AGLOMERASI DAN PERBEDAAN PRODUKTIVITAS PERUSAHAAN DI DALAM DAN DI LUAR KAWASAN BERIKAT - Suharyani, Suharyani; Mahi, Benedictus Raksaka (Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
Export promotion policies have been implemented in many developing countries, which is implemented as Bonded Zone in Indonesia. There are at least two interesting issues from the Bonded Zone’s existence, related to industrial agglomeration and tax incentives with export share requirement. This study aims to look at the impact of agglomeration on productivity differences between firms located within and outside the Bonded Zone. The object were exporters in industrial sector, while the period was from 2009 to 2016. This study uses twostep Heckman method to overcome the selection bias problem because the usage of tax reporting data. The first phase was probit model of tax compliance equation, while productivity equation in the second stage was estimated using OLS. The estimation outputs show firms within the Bonded Zone are more productive because they receive benefits from industrial agglomeration within the zone, from availability of facilities and infrastructure, labor access and knowledge spillover. As a policy recommendation, economic policies in Indonesia should be directed in the form of place-based policies because they are proven to be able to increase productivity.Keywords: Bonded Zone, productivity, agglomeration, tax incentive, twostep HeckmanJEL classification: H2, H21, F10